2009
DOI: 10.1016/j.gloplacha.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sea level budget over 2003–2008: A reevaluation from GRACE space gravimetry, satellite altimetry and Argo

Abstract: From the IPCC 4th Assessment Report published in 2007, ocean thermal expansion contributed by ∼ 50% to the 3.1 mm/yr observed global mean sea level rise during the 1993-2003 decade, the remaining rate of rise being essentially explained by shrinking of land ice. Recently published results suggest that since about 2003, ocean thermal expansion change, based on the newly deployed Argo system, is showing a plateau while sea level is still rising, although at a reduced rate (∼ 2.5 mm/yr). Using space gravimetry ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
217
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(232 citation statements)
references
References 34 publications
10
217
0
5
Order By: Relevance
“…They accept as a reasonable estimate for the GIA-related mass rate correction over the oceans, a value of À1.0 mm yr À1 which is approximately a factor of 2 smaller in magnitude than the value delivered by the ICE-5G (VM2) model listed here in Table 1 and discussed more fully by Peltier [2009]. The Peltier [2009] value has previously been accepted by Cazenave et al [2009] as being required to achieve closure of the budget. Although Leuliette and Miller [2009] claim that they also achieve closure of the budget using a value for the GIA correction of À1.0 mm yr À1 , a value attributed to Paulson et al [2007], it will be clear that their own analysis would be markedly improved if they were to employ the ICE-5G(VM2) value for the GIA correction.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…They accept as a reasonable estimate for the GIA-related mass rate correction over the oceans, a value of À1.0 mm yr À1 which is approximately a factor of 2 smaller in magnitude than the value delivered by the ICE-5G (VM2) model listed here in Table 1 and discussed more fully by Peltier [2009]. The Peltier [2009] value has previously been accepted by Cazenave et al [2009] as being required to achieve closure of the budget. Although Leuliette and Miller [2009] claim that they also achieve closure of the budget using a value for the GIA correction of À1.0 mm yr À1 , a value attributed to Paulson et al [2007], it will be clear that their own analysis would be markedly improved if they were to employ the ICE-5G(VM2) value for the GIA correction.…”
Section: Discussionmentioning
confidence: 79%
“…As shown explicitly in section 5, the action of such modern ice sheet melting has a significant impact on Earth rotation. Models of modern land ice melting such as those constrained by GRACE itself [e.g., Cazenave et al, 2009;Peltier, 2009] for the polar regions and by Meier et al [2007] for the small ice sheets and glaciers, must be shown to pass the test provided by the GRACE observations. However, the ICE-5G (VM2) model, and the modest improvements to it that are currently under construction, are precisely the models required to filter ice age influence from these modern space geodetic observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Quantification of the increase or decrease of the ice and snow masses in the polar or large glacier areas has been achieved by scientists who were able to demonstrate a strong correlation between the climatic phenomenon ENSO / La Nina, the rainfall patterns in West Antarctica and the reduction of ice mass there (Sasgen et al 2010).  Monitoring of global mean eustatic sea-level variations as a consequence of mass re-distribution between continents and ocean basins for the partitioning of observed sea-level changes into mass and temperature contributions (Cazenave et al 2009), as well as the regional re-distribution of water masses in response to time-variable surface winds that are tightly connected to time-variations of hemispheric current systems such as the Antarctic Circumpolar Current (Bergmann and Dobslaw (2012)).  Observation of changes in the solid Earth following large earthquakes, such as Sumatra-Andaman (2004), Chile (2010) and Fukushima (2011, Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cazenave et al 2009;Milne et al 2009;Church et al 2011) and efforts are underway to improve projections of the contributions of ice to future sea-level change (e.g. www.ice2sea.eu).…”
Section: Introductionmentioning
confidence: 99%